2016
DOI: 10.1016/j.molmet.2016.01.009
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-domain tagging implicates caveolin-1 in insulin receptor trafficking and Erk signaling bias in pancreatic beta-cells

Abstract: ObjectiveThe role and mechanisms of insulin receptor internalization remain incompletely understood. Previous trafficking studies of insulin receptors involved fluorescent protein tagging at their termini, manipulations that may be expected to result in dysfunctional receptors. Our objective was to determine the trafficking route and molecular mechanisms of functional tagged insulin receptors and endogenous insulin receptors in pancreatic beta-cells.MethodsWe generated functional insulin receptors tagged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 73 publications
2
49
1
Order By: Relevance
“…Herein, we observed a significant degree of overlap between NECC2 and IR immunosignals at the cell surface. Several studies have shown that this receptor may undergo internalization after insulin stimulation . However, we observed that the colocalization rate between NECC2 and IR did not decrease in 3T3‐L1 adipocytes exposed to insulin, but an increase in NECC2 accumulation at the cell surface, suggesting that this hormone induces the recruitment of NECC2 to the cell surface.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Herein, we observed a significant degree of overlap between NECC2 and IR immunosignals at the cell surface. Several studies have shown that this receptor may undergo internalization after insulin stimulation . However, we observed that the colocalization rate between NECC2 and IR did not decrease in 3T3‐L1 adipocytes exposed to insulin, but an increase in NECC2 accumulation at the cell surface, suggesting that this hormone induces the recruitment of NECC2 to the cell surface.…”
Section: Discussioncontrasting
confidence: 60%
“…Thus, overexpression of NECC2 in 3T3‐L1 cells produced a sustained stimulation of insulin‐activated phosphorylation of Akt. Notably, NECC2 overexpression had no effect on IR‐dependent activation of ERK1/2, which is also mediated via insulin binding to IR, but has been shown to occur during IR receptor internalization in endosomes . On the other hand, down‐regulation of NECC2 impaired insulin‐induced phosphorylation of both Akt and the major ERK isoform, ERK2 .…”
Section: Discussionmentioning
confidence: 94%
“…Insulin resistance within tissues can arise at multiple levels of the insulin signaling pathway (Johnson & Olefsky 2013). Insulin resistance can also be caused by insulin receptor desensitization and removal from the plasma membrane (Knutson et al 1983, Boothe et al 2016.…”
Section: Hyperinsulinemia In the Etiology Of Insulin Resistance And Tmentioning
confidence: 99%
“…Ptrf is known for its role in the formation and organization of caveolae, together with caveolin proteins, which have also been implicated in lipodystrophy (27)(28)(29). In addition to clathrin, phosphorylated caveolin-1 has been implicated recently in insulin uptake and insulin receptor internalization (30,31). However, we did not observe significant differences in the protein abundances of clathrin, caveolin 1 (Cav1), Y14 phosphorylated Cav1, insulin receptor, phosphorylated-Akt, or phosphorylated-Erk between control littermates and experimental mice.…”
Section: Markers Of Lipid Mobilization Are Altered After Induced Insumentioning
confidence: 99%